Effectiveness of Systemic and Topical Combination Therapy for the Treatment of Pustular Psoriasis: A Meta-Analysis Study - Muhammad Yusuf (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Pustular psoriasis is a rare and severe variant of psoriasis, characterized by sterile pustules that appear over erythematous plaques. Treatment is challenging and often requires a combination of systemic and topical therapy. This meta-analysis study aims to evaluate the effectiveness of systemic and topical combination therapy for the treatment of pustular psoriasis. Methods: Relevant publications were identified through electronic searches in PubMed, Scopus, and Web of Science. Studies evaluating the effectiveness of systemic and topical combination therapy for the treatment of pustular psoriasis were included. Data were extracted and analyzed using random effects statistics. Results: A total of 10 studies with a total of 324 patients were included in the analysis. Systemic and topical combination therapy demonstrated significant effectiveness in improving pustular psoriasis plaque improvement (PASI 75: 58% vs. 23%, p<0.001) and time to recurrence (12 months vs. 6 months, p<0.001) compared with systemic therapy or single topical. The most common side effect is skin irritation, which occurs in 15% of patients. Conclusion: Systemic and topical combination therapy is an effective treatment option for pustular psoriasis. The choice of therapy should be based on the individual characteristics of the patient. Further research is needed to optimize the combination of agents and to evaluate long-term effectiveness.